PENERAPAN MODEL PJBL UNTUK MENINGKATKAN KEMAMPUAN SISWA PADA MATERI HAK DAN KEWAJIBAN KELAS IV DI SD 066055 MEDAN DENAI - Clara Susanty Zebua; Ambar Wulan Sari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Students must be able to achieve the objectives of their learning. If students have not achieved the learning objectives, then an action must be taken to achieve the learning objectives. Furthermore, this is reflected in the results of improving students' abilities in their learning. This research is in the form of classroom action research (CAR), which is carried out to improve students' abilities in learning rights and obligations in PPKN learning using the Project-Based Learning (PJBL) learning model. The implementation of this PJBL model can change and improve students' learning abilities. The method used in this classroom action research is the Kemmis and Mc.Ditagrat models, each cycle consists of four stages, namely planning, implementation, observation, and reflection. The design of this research began with observations in class IV at SDN 066055 Medan Denai. Students in the pre-cycle reached 25% for the achievement of cycle I reaching 50%, and cycle II completion reaching 87%.